Direct and inverse theorems on the approximation of almost periodic functions in Besicovitch-Stepanets spaces - Serdyuk, A.S.; Shidlich, A.L. (Carpathian Mathematical Publications, 2021)
Direct and inverse approximation theorems are proved in the Besicovitch-Stepanets spaces BS^p of almost periodic functions in terms of the best approximations of functions and their generalized moduli of smoothness.